2018
DOI: 10.1186/s13006-018-0174-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mother and newborn early skin-to-skin contact on initiation of breastfeeding, newborn temperature and duration of third stage of labor

Abstract: BackgroundMother and newborn skin-to-skin contact (SSC) after birth brings about numerous protective effects; however, it is an intervention that is underutilized in Iraq where a globally considerable rate of maternal and child death has been reported. The present study was conducted in order to assess the effects of SCC on initiation of breastfeeding, newborn temperature, and duration of the third stage of labor.MethodsA quasi-experimental study was conducted on 108 healthy women and their neonates (56 in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
98
0
23

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(128 citation statements)
references
References 25 publications
7
98
0
23
Order By: Relevance
“…Mothers who received SSC in EENC implementation experienced shorter median time to initiate breastfeeding (25 min vs. 33 min) and were more likely to ensure first-time breastfeeding (OR=5.53). Similar findings have been reported in previous studies carried out by Caitlin et al in the USA, Iabal et al in Pakistan, and Kolssoom et al in Iraq [28][29][30]. This could be explained by a strong biological mechanism.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Mothers who received SSC in EENC implementation experienced shorter median time to initiate breastfeeding (25 min vs. 33 min) and were more likely to ensure first-time breastfeeding (OR=5.53). Similar findings have been reported in previous studies carried out by Caitlin et al in the USA, Iabal et al in Pakistan, and Kolssoom et al in Iraq [28][29][30]. This could be explained by a strong biological mechanism.…”
Section: Discussionsupporting
confidence: 91%
“…Our analysis also suggested that prolonged duration of SSC (21.53 min) and first-time breastfeeding (4.16 min) occurred concomitant with the introduction of EENC. Longer duration of the first breastfeed in mothers receiving EENC results from sustained mother and newborn SSC, by which increased breast milk production prolongs duration of first-time breastfeeding [22], and then enhanced maternal satisfaction may occur [28][29][30]. These findings favored WHO's recommendation that "SSC should begin ideally at birth and last continually until the end of the first breastfeeding" [13,34].…”
Section: Discussionmentioning
confidence: 99%
“…Faced with this issue, the results showed that the lack of skin-to-skin contact between the mother and her newborn limits the early onset of breastfeeding, as in the results of the study by Kolsoom et al (2018) 32 showed an association between skin-to-skin contact between mothers and their newborns and early onset of breastfeeding (OR 2.86, 95% CI 1.68, 4.85), which also it was reported by Aghdas et al (2014) 33 . Additionally, Moore, Anderson, Bergman (2007) 34 , in a systematic review that included 30 controlled clinical trials with 1,925 mother and child dyads, they found that skin-to-skin contact had positive effects on breastfeeding up to 4 months after delivery and on the duration of the same, in accordance with the Clinical Practice Guidelines 20 that considered this high-quality scientific evidence and recommend that women maintain skin-to-skin contact with their children immediately after birth.…”
Section: Discussionmentioning
confidence: 81%
“…Drying and wrapping the newborn instantly after birth and initiation of skin to skin contact of the mother and the newborn are proven interventions to limit hypothermia which is the leading cause of morbidity and mortality of neonates especially in the developing countries (35). Drying the newborn within ten minutes after birth was reported by 68.8% of the respondents, while 57% of the newborn mother duo had skin to skin contact within ten minutes of birth.…”
Section: Discussionmentioning
confidence: 99%